"PHILOLOGICAL TUESDAYS" OF THE INSTITUTE OF PHILOLOGY, JOURNALISM AND INTERCULTURAL COMMUNICATION, SOUTHERN FEDERAL UNIVERSITY (Proceedings of Southern Federal University. Philology, 2014)
The journal's Editorial BoardKeywords: a series of lectures, philology, lecture, presentation, university.This article focuses on the cycle of open lectures for citizens, devoted to the topical issues of philology, which was launched in October, 2013 in the framework of the educational project "University is for the city". This event took place in the Institute of philology, journalism and intercultural communication. The author briefly recounts the activities of the event and stresses that the lectures, accompanied with colorful presentations, caused a vivid interest among the public .